(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article presents the results of the study of parents’ awareness of the issues of raising children with psychophysical developmental disorders. The importance of this study is primarily determined by the fact that the family has an important role both in the upbringing, education and development of these children, and in their adaptation and integration into society. Therefore, the awareness of parents in matters of upbringing and carrying out correctional and developmental work with children with psychophysical developmental disorders is of very important practical importance. The importance of the problem under study is also determined by the fact that with the birth in a family of a child with impaired psychophysical development, many unforeseen problems and difficulties appear in the construction of educational and correctional - developmental work. And the success in organizing and conducting educational and correctional - developmental work with this child depends on the level of development of parents’ awareness of these issues. Therefore, the study of the level of parents’ awareness of the upbringing of children with psychophysical developmental disorders makes it possible to identify the peculiarities of the parental attitude towards these children, their possibilities in carrying out educational work with them. The foregoing determines the relevance of this study, its theoretical and practical significance. The results of the research made it possible to note that, on the one hand, parents with a child with impaired psychophysical development understand the importance of timely provision of qualified assistance to a child, on the other hand, insufficient awareness of parents in these matters makes it difficult to carry out educational and correctional - developmental work with these children in family conditions.